ANALISIS KESALAHAN PESERTA DIDIK DALAM PEMECAHAN MASALAH FUNGSI KOMPOSISI - Naibaho, Susilawati Br; Laamena, Christina M; Mataheru, Wilmintjie (Program Studi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Pattimura, 2023)
This study aims to describe the mistakes of class X students of SMAN 9 Ambon in solving composition function problems. This type of research is qualitative descriptive research. The study was conducted on 3 subjects, each of which was high, medium, and low which was taken based on test results and educators' considerations about students' communication skills. The analysis of student errors is classified according to mathematical objects (facts, concepts, principles, and operations) in using Polya's problem-solving steps. The instruments used in this study test sheets and interview guidelines included the researcher as the main instrument. The results showed that subjects were highly capable of solving the 3 problems given and did not perform indicators of errors of mathematical objects in solving problems. The capable subject is solving 3 questions and performing three indicators of errors in problem solving, namely facts, concepts, and principles. Low-ability subjects solve 3 questions and perform four indicators of errors in problem solving, namely facts, concepts, principles, and operations. From the results of the work and the results of student interviews, mistakes are not only made by low-ability learners or high error subjects, but in high-ability learners or low-error subjects and also medium-capable learners there are still mistakes made in solving problems about composition function